Manufacturing method affects mitochondrial DNA release and extracellular vesicle composition in stored red blood cells. Issue 1 (25th February 2016) - Bakkour, S.; Acker, J. P.; Chafets, D. M.; Inglis, H. C.; Norris, P. J.; Lee, T.‐H.; Busch, M. P.
Abstract : Background and Objectives: Damage‐associated molecular patterns (DAMPs) are found in transfusion products, but their potential impacts are not fully understood. We examined the influence of manufacturing method on levels of mitochondrial (mt) DNA and extracellular vesicle (EV) DAMPs in red cell concentrates (RCCs). Materials and Methods: Eighty‐seven RCCs were prepared using nine different methods (6–15 units/method), including three apheresis, five whole blood (WB)‐derived leucoreduced (LR) and one WB‐derived non‐LR method. On storage days 5 and 42, levels of mtDNA (by PCR) and number and cell of origin of EVs (by flow cytometry) were assessed in RCC supernatants. Results: There was a 100‐fold difference in mtDNA levels among methods, with highest levels in non‐LR, followed by MCS+ and Trima apheresis RCCs. There was a 10‐fold difference in EV levels among methods. RBC‐derived CD235a+ EVs were found in fresh RCCs and increased in most during storage. Platelet‐derived CD41a+ EVs were highest in non‐LR and Trima RCCs and did not change during storage. WBC‐derived EVs were low in most RCCs; CD14+ EVs increased in several RCCs during storage. Conclusion: DAMPs in RCCs vary by manufacturing method. MtDNA and EV could be informative quality markers that may be relevant to RCC immunomodulatory potential.